The design of a volleyball training drill: definition of parameters and assessment of drills' contents - Thiago Machado; Wellington Rangel; Leonardo Lamas (Colégio Brasileiro de Ciências do Esporte, 2021)
ABSTRACT The aim of this work was to define a model of volleyball drills' structure. A set of parameters has been designed and tested for: i) pertinence and accuracy; ii) criteria reliability; iii) practical application. Expert judges evaluated model's pertinence, accuracy and criteria reliability. A sample of 50 drills was assessed for drills' analysis. The model demonstrated pertinence and accuracy, with complete agreement among experts. Criteria were reliable (Kappa test results > 0.8). Analysis indicated significant differences in the frequency of model's parameters (graph topology), for instance among attributes (basic complex - 30%) with manifold drills (46,7%) in the technical domain (100%). The model contributes with theoretical support for a coach's key task of designing practice contents.